2013
DOI: 10.1080/19443994.2013.770114
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Orange II dye from aqueous solutions using phosphoric-acid modified clam shell powder

Abstract: In this study, the clam shell, a waste biomaterial, was modified with phosphoric acid to improve the adsorption amount of Orange II dye. The effects of initial concentration, contact time, and temperature on the adsorption were studied. The equilibrium adsorption data of Orange II on the phosphoric acid-modified clam shell powder (PCSP) were adequately represented by Langmuir isotherm with an adsorption capacity of 1,017.13 mg/g, which is higher than that obtained using raw clam shell powder. Adsorption kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…More precisely, the bands at 1626 and 1577 cm −1 and at 1448 and 1382 cm −1 correspond to the asymmetric and symmetric stretching vibrations of the carboxylate groups in BTC, respectively. The adsorption of the dye on the Fe(BTC) material is confirmed by FTIR spectroscopy which displays the characteristic bands of both Orange II dye [15] and Fe(BTC) material [34] (Figure 2b). In the FTIR spectrum of Orange II dye, the weak band at 1037 cm −1 corresponds to the –N=N– bond stretching vibration and the band at 1209 cm −1 is assigned to the –C–O– bond stretching vibration [16] (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%
“…More precisely, the bands at 1626 and 1577 cm −1 and at 1448 and 1382 cm −1 correspond to the asymmetric and symmetric stretching vibrations of the carboxylate groups in BTC, respectively. The adsorption of the dye on the Fe(BTC) material is confirmed by FTIR spectroscopy which displays the characteristic bands of both Orange II dye [15] and Fe(BTC) material [34] (Figure 2b). In the FTIR spectrum of Orange II dye, the weak band at 1037 cm −1 corresponds to the –N=N– bond stretching vibration and the band at 1209 cm −1 is assigned to the –C–O– bond stretching vibration [16] (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%
“…Dyes have been widely used in several industries, such as textiles, leather, paper, printing, cosmetics and so on, which, however, lead to serious environmental problems (Ma et al, 2013). Especially, in printing and dyeing industries, a considerable amount of effluent is generated, which contains aromatic, polycyclic aromatic or heterocyclic dye, toxic, and carcinogenic compounds that are difficult to be removed and biodegraded (Crini, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Especially, in printing and dyeing industries, a considerable amount of effluent is generated, which contains aromatic, polycyclic aromatic or heterocyclic dye, toxic, and carcinogenic compounds that are difficult to be removed and biodegraded (Crini, 2006). Therefore, dye removal is an important and challenging area in wastewater treatment (Ma et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It can be concluded that the studied layered double hydroxides are more efficient adsorbent materials for Orange II removal, than other adsorbents reported in literature due to the fact that in this case the equilibrium is achieved more quickly. In case of Orange II adsorption onto metal-Organic Framework (MOF) iron-benzenetricarboxylate (Fe(BTC)), the equilibrium is achieved between 80 and 140 min (García et al, 2014) and through adsorption onto phosphoric-acid modified clam shell powder after 90 min of stirring (Ma et al, 2013).…”
Section: At Different Temperaturesmentioning
confidence: 99%